Advancing imaging biomarker development and translation through the National Cancer Imaging Translational Accelerator (NCITA) - McAteer, M; Higgins, G (Research Outreach, 2022)
It is estimated that someone is diagnosed with cancer every two minutes in the UK. Clinical imaging offers a minimally invasive way of diagnosing and managing a variety of cancers. The National Cancer Imaging Translational Accelerator (NCITA) consortium now provides researchers with the infrastructure to conduct high-quality, multi-centre clinical research in the quest to develop standardised imaging biomarkers and accelerate their translation into clinical use. The NCITA consortium and collaborators aim to improve clinical outcomes for patients through early cancer identification and new treatment discoveries.